Desenvolvimento, distribuição de renda e capital estrangeiro: um comentário sobre a Cepal nos anos 50 - Colistete, Renato Perim [UNESP] (Centro de Economia Política, 2023)
This article discusses the ECLAC’s approach on the role of foreign capital in the industrialisation of the Latin America during the fifties. The first section provides a synthesis of Eclac’s vision on the structural changes in the main Latin American economies. The second section shows how the international capital was understood by “cepalinos” thinkers as an alternative way of financing development, in opposition to the radical schemes that were proposed by the nationalists and the left. The concluding section summarizes the main points of the paper.

Este artigo discute a abordagem da Cepal sobre o papel do capital estrangeiro na industrialização da América Latina nos anos cinquenta. A primeira seção fornece uma síntese da visão da Cepal sobre as mudanças estruturais nas principais economias latino-americanas. A segunda seção mostra como o capital internacional foi entendido pelos pensadores “cepalinos” como uma maneira alternativa de financiar o desenvolvimento, em oposição aos esquemas radicais propostos pelos nacionalistas e pela esquerda. A seção final resume os principais pontos do artigo.
Development, distribution of income and foreign capital: a comment on ECLAC in the 1950s
Keywords: History of economic thought; economic growth; História do pensamento econômico; crescimento econômico